(untitled) (Global Journal of Management and Business Research, 2011)
Previous research examining mixed duopoly shows that the use of an incentive contract for the public firm increases welfare and that privatization reduces welfare. This paper is built from Barros (1995) model by investigating and deriving the optimal incentive contracts when the public domestic firm competes not with domestic private firm but instead with a private foreign firm. We show that by giving the public manager an incentive contract based on linear combination of welfare and profit, welfare increases. Indeed, for less weight on profit given that the private firm is foreign instead of domestic, the optimal delegation contract is actually lower than that in the traditional duopoly (Barros 1995). On the other hand, the effect of privatization in this case is more complex, it depends on marginal cost.